A World Proof Life: Eleanor Dark, a writer in her times, 1901-1985 ﻿ - Marivic Wyndham (UTS ePRESS, 2007)
Eleanor Dark (1901-1985) is one of Australia's most celebrated writers of the inter-war years. Born with the twentieth century - a Federation baby - she published ten novels, amongst them one of the best loved Australian stories of all time, The Timeless Land. Her life spanned successive global crises - two world wars, the economic depression of the 1930s, the Cold War - each issuing its own challenges to the artist and the people's writer she thought herself to be. By far the most privileged writer of her generation, her ultimate challenge was a personal one: to unlock the gates of her world-proof life to a society and a world in crisis. The first cross-cultural biography of this famous Australian writer, Marivic Wyndham's rich and controversial portrait of Eleanor Dark is based on extensive research of the author's public and private lives.